2019
DOI: 10.17507/jltr.1001.07
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions about Self-recording Videos to Develop EFL Speaking Skills in Two Ecuadorian Universities

Abstract: The present study explores the perceptions of EFL students from two Ecuadorian universities on the use of Self-Recording Videos (SRV) to develop speaking skills.  As students do not have the opportunity to talk in the target language outside their classes, the authors of the present study analyzed the participants’ viewpoints regarding SRV to improve their conversational abilities.  There is still limited research on the use of SRV for English speaking practice in a foreign country, so the researchers' purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 8 publications
4
20
0
1
Order By: Relevance
“…In another study, Encalada and Sarmiento (2019) reported that students expanded their vocabulary, increased pronunciation accuracy and became more confident in their ability to speak English through selfrecording video. Kirkgöz's (2011) students not only expanded their vocabulary knowledge but also enhanced their oral skills (i.e., fluency, pronunciation, vocabulary, accuracy and task accomplishment) after utilising video-recorded speaking tasks.…”
Section: Video Projects In Efl Learningmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study, Encalada and Sarmiento (2019) reported that students expanded their vocabulary, increased pronunciation accuracy and became more confident in their ability to speak English through selfrecording video. Kirkgöz's (2011) students not only expanded their vocabulary knowledge but also enhanced their oral skills (i.e., fluency, pronunciation, vocabulary, accuracy and task accomplishment) after utilising video-recorded speaking tasks.…”
Section: Video Projects In Efl Learningmentioning
confidence: 98%
“…Since the early 2010s, researchers have applied vlog projects in language learning and shown their educational benefits in EFL classrooms (Aldukhayel, 2019;Encalada & Sarmiento, 2019;Gromik, 2012Gromik, , 2015Hung, 2011;Yang & Wu, 2012). Vlogs are made by people who use mobile devices or smartphones with video camcorder capabilities to film videos and upload them to online video platforms for audiences to watch (Snelson, 2015).…”
Section: Video Projects In Efl Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-made video becomes the platform for students to practice and learn throughout the speaking course, which helps them in improving their professional public speaking skills such as enunciation, articulation, facial expression, posture, and gestures. Meanwhile the benefits from the self-recording video (SRV) are mentioned by Encalada and Sarmiento (2019) as follows: providing opportunities to practice the theories and knowledge they gain in the classroom which leads to vocabulary and pronunciation improvement; allowing improvisation which makes students feeling motivated while preparing the SRVs; encouraging students to speak in English with less fear. This also supports the statement from Mahmoud and Ghallab (2020) who reported that utilizing technology allows students to develop their language skills in general and also specific skills in the language they are learning.…”
Section: Asmentioning
confidence: 99%
“…The difference is only on the platforms used to communicate, since the speaking activity can be done directly in traditional classroom meanwhile in online courses students need to upload it through the web 2.0 technologies Previous researchers have conducted researches about utilizing the Web 2.0 technologies in speaking classes to drill students' speaking skills and to give them new experiences in learning (Jafari & Chalak, 2016;Lara Olivo, Yumi Guacho, Padilla Padilla, & Padilla Padilla, 2020;Minalla, 2018;Mustafa, 2018). Meanwhile other researches mentioned reports on assessing students' skills using various rubrics (Encalada & Sarmiento, 2019;Schreiber, Paul, & Shibley, 2012;Yükselir & Kömür, 2017). However, research about exploring teachers' experience in assessing students' speaking skills using specified rubric through the self-recorded video uploaded to the Web 2.0 technologies is still limited.…”
Section: Asmentioning
confidence: 99%